Countermeasures Against The Criminal Act Of Runaway Underage Girls - Bella Putri Hunowu (Universitas Negeri Gorontalo, 2021)
This study aims to determine the prevention of criminal acts of escaping underage girls. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling and using descriptive analysis techniques. The results of this study show the efforts made by the police, namely, first, taking preventive measures by providing socialization to the community about the dangers of the child's environment if not supervised by parents, besides that other preventive forms invite the community to cooperate in supervising actions that can harm children. who are underage. Second, take repressive actions against perpetrators who run away underage children and cooperate with police agencies in certain areas, this can make it easier for the police to speed up the legal process, especially if the perpetrators run away. Third. Maximizing cooperation between the families of the victims in order to make it easier for investigators to collect evidence. So that related parties can maximize the socialization of negative impacts, both in general and specifically regarding the legal consequences, so that all levels of society can actively participate in general with the police in efforts to tackle the crime of escaping underage girls.